2020
DOI: 10.5430/ijfr.v11n2p173
|View full text |Cite
|
Sign up to set email alerts
|

Chief Executive Officer Characteristics and Financial Restatements in Malaysia

Abstract: The purpose of this paper is to investigate whether the Chief Executive Officer (CEO) characteristics affect the occurrence of financial restatements in Malaysian firms. The CEO characteristics used in this study were tenure, honorific title, gender, expertise, and age. In addition, the financial restatement has been measured as a dummy variable as to whether companies restate their financial statements or not. The sample of this study comprised 442 companies listed in the main market of Bursa Malaysia during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
(70 reference statements)
0
7
0
2
Order By: Relevance
“…The BoD is responsible for the high-quality financial reports to stakeholders (Brochet & Srinivasan, 2014;Omer et al, 2019). BoD size is considered to determine the quality of financial information submitted to the public (Altarawneh et al, 2020). The larger size is considered to have higher reporting quality (Hasnan et al, 2020).…”
Section: Hypotheses Development Bod Size and Financial Restatementmentioning
confidence: 99%
See 2 more Smart Citations
“…The BoD is responsible for the high-quality financial reports to stakeholders (Brochet & Srinivasan, 2014;Omer et al, 2019). BoD size is considered to determine the quality of financial information submitted to the public (Altarawneh et al, 2020). The larger size is considered to have higher reporting quality (Hasnan et al, 2020).…”
Section: Hypotheses Development Bod Size and Financial Restatementmentioning
confidence: 99%
“…Women have thoroughness and discipline, and they can maintain the work quality. A woman also tends to avoid risk, trying to minimize mistakes (Altarawneh et al, 2020). Therefore, at least one female director directs their group on process and control-oriented.…”
Section: Female Bod and Financial Restatementmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the level of board independence or audit quality has an impact on the likelihood of a listed company's financial restatement (Hasnan, 2015). In addition, Marwan Altarawneh's (2020) research evaluated the CEO characteristics influencing the occurrence of financial restatement (Altarawneh et al, 2020); and Francis and Yu's (2013) thesis demonstrated that the audit quality from the Big 4 accounting firms can affect the financial restatement of listed companies as well (Francis, 2013). (Bhattacharya, 1979) In Vietnam, it is emphasized that Nguyen Van Huong's (2018) research can summarize these factors that may have an impact on the financial restatements of listed companies in Vietnam's stock market.…”
Section: Prior Studies On Financial Restatementmentioning
confidence: 99%
“…Selain itu, juga ada Riandi et al (2019) yang meneliti tentang hubungan penyajian kembali dengan nilai wajar, serta Siregar dan Rahayu (2018) yang melakukan penelitian pengaruh corporate governance terhadap restatement dan dampaknya terhadap harga saham. Masa jabatan dan gender dari CEO juga memiliki pengaruh signifikan terhadap penyajian kembali (Altarawneh et al, 2020).…”
unclassified